Experimental study of the out-of-plane dynamic compression of hexagonal honeycombs - Xu, Shanqing. (2013)
The out-of-plane crushing behaviour of four types of aluminium hexagonal honeycombs was extensively investigated over a wide range of strain rates where each test was conducted at a constant compressive velocity. The effects of specimen dimensions, relative density, strain rate and honeycomb cell size on the mechanical properties of honeycombs were studied. It was demonstrated that the mean plateau force was linearly related to the specimen dimensions. However, the calculated plateau stress varied with specimen dimensions and a minimum of 9 9 cells should be used in order to represent the bulk properties of honeycombs. A large strength enhancement of honeycombs was observed when the relative density and strain rate increased. The tangent modulus also increased towards the end of the crushing process, especially for those honeycombs with small values of wall thickness to edge length ratio (t/l). Semi-empirical relations were obtained to describe the effects of relative density (t/l ratio) and strain rate on the plateau stress. The difference in deformation patterns for honeycombs between quasi-static and dynamic loading conditions was also discussed.